Design of an Artificial Intelligence Robot as a Tool for Teaching Media Based On Contextual Teaching and Learning - Muhamad Syariffuddien Zuhrie; Ismet Basuki; I G P Asto B; Lilik Anifah (Faculty of Engineering, Universitas Negeri Yogyakarta, 2017)
This study was conducted by applying a research and development design with the aim of producing a learning tool in the form of Artificial Intelligence robot module and kit based on Contextual Teaching and Learning at the Department of Electrical Engineering to improve the students’ skills. This was a development research adopting 4-D model, proposed by Thiagarajan and Semmel (1974) that consisted of four stages: Define, Design, Develop, and Disseminate. Data of the Indonesia Robot Contest during the period 2009-2015 reveals that the developed modules have reached the fourth stage of 4-D research model that is dissemination thus, the module is considered perfect, ready to be duplicated and distributed as a learning device for Artificial Intelligence robotics courses. While, the developed module was validated with the average assessment score of 3.34. The module is expected to be able to produce Artificial Intelligence Robot Tool for teaching based on Contextual Teaching and Learning to improve the students’ skills to be applied in the field. In the results, students also showed positive responses on the robotics module and Contextual Teaching and Learning strategy.